Fenomen pamięci w twórczości Antona Czechowa - Chudzińska-Parkosadze, Anna (Studia Rossica Posnaniensia, 2012)
This article focuses on the phenomenon of memory as reflected both in Chekhov’s dramas and works of prose. The phenomenon of memory manifests itself by referring to the main ideas in Chekhov’s poetics: bond of times (past – the present time – future), eternity, suffering, artistic work, happiness, life and death, and the truth of life. However, examining a given phenomenon requires attentive reading because Chekhov counts on an attentive reader who is able to capture the essence among the details of everyday life.